Analisis Pendistribusian Zakat Produktif Pada Lembaga Amil Zakat Nasional Inisiatif Zakat Indonesia Cabang Sumatera Utara - Nurjannah Nurjannah; Reni Ria Armayani Hasibuan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2022)
Zakat in Islam is assets that must be issued if it meets the requirements and is an obligation that must be fulfilled by all Muslims. Zakat acts in part as a tool given by Islam to alleviate poverty by making the rich aware of their social responsibilities. There are two types of zakat distribution in Indonesia: consumption distribution and production distribution. So far, the actual distribution of zakat is more dominated by consumptive zakat distribution. The purpose of this study was to identify the mechanism for distributing productive zakat at LAZNAS IZI North Sumatra Branch and the impact of distributing productive zakat funds on mustahik status. Data collection methods used are primary and secondary data sources. Data collection techniques and tools were carried out through interviews and documentation. The results showed that the instrument of the productive zakat distribution mechanism of LAZNAS IZI North Sumatra Branch was running well when distributing productive zakat to mustahik and still using the grant contract. That is, productive zakat money to mustahik offered to mustahik is given free of charge. The impact of productive zakat funds on mustahik status cannot completely change mustahik into muzakki. The status of new mustahik can change into muktafi (people who can fulfill their needs) and munfik (people who donate or give charity). Keywords: productive zakat, zakat distribution, amil zakat institutions